2018
DOI: 10.1002/cbic.201800246
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Substrate Selectivity of the Hypoxia‐Inducible Factor Prolyl Hydroxylase 2 Catalytic Domain

Abstract: In animals, the response to chronic hypoxia is mediated by upregulation of the α,β-heterodimeric hypoxia-inducible factors (HIFs). Levels of HIFα isoforms, but not HIFβ, are regulated by their post-translational modification as catalysed by prolyl hydroxylase domain enzymes (PHDs). Different roles for the human HIF-1/2α isoforms and their two oxygen-dependent degradation domains (ODDs) are proposed. We report kinetic and NMR analyses of the ODD selectivity of the catalytic domain of wild-type PHD2 (which is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 35 publications
5
10
0
Order By: Relevance
“…S6B ). As reported ( 60 , 61 ), HsPHD2 catalyzed little 2OG turnover (<10% in 1 h) in the presence (or absence) of any of the Skp1 proteins ( Fig. S6C ).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…S6B ). As reported ( 60 , 61 ), HsPHD2 catalyzed little 2OG turnover (<10% in 1 h) in the presence (or absence) of any of the Skp1 proteins ( Fig. S6C ).…”
Section: Resultssupporting
confidence: 84%
“…Notably, HsSkp1 E147P induced the most efficient 2OG turnover with TgPhyA ( Figure S6b). As reported (60,61), HsPHD2 catalyzed little 2OG turnover (< 10 % in an hour) in the presence (or absence) of any of the Skp1 proteins ( Figure S6c). By contrast with HsPHD2 and DdPhyA, TgPhyA exhibited substantial 'uncoupled' 2OG turnover in the absence of substrate, with > 80 % 2OG turnover being observed by NMR within an hour, in the presence of L-ascorbate ( Figure S6d).…”
Section: Og Turnover By Ddphya Tgphya and Hsphd2supporting
confidence: 74%
See 2 more Smart Citations
“…It has been shown that the hydroxylation of either CODD or NODD may lead to the degradation of HIF1α [39,40] . Although NODD hydroxylation is more sensitive to changes in oxygen concentration than CODD hydroxylation, [41] kinetics and binding studies showed that CODD is the preferred substrate and is a stronger binder of PHDs than NODD, which is also supported by structural studies [42–45] …”
Section: Peptidyl Substrate Km/μm Kd/μm Ic50/μmmentioning
confidence: 74%